On a Romantic Island: Shakespeare and Mamma mia - Wild, Jana B. (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
The paper concerns the blockbuster musical film Mamma mia, loosely using some of Shakespearean patterns, topoi and plots. Set on a small Greek island, idylic and exotic, the film offers a contemporary romantic story with new/reversed roles in terms of gender, parenthood, sexuality, marriage and age, pointing to a different cultural paradigm. While the Shakespearean level is recast, remixed and probably less visible, the priority is given to the utopia of the 1970s and to the question of its outcome and transformation.